Adapting to Radical Change: Strategy and Environment in Piece-Rate Adoption During China's Transition - Keister, Lisa A. (Organization Science, 2002)
Adaptation to radical change is central to research in organization theory, and some of the most dramatic examples of environmental change have occurred recently in transition economies such as China. I take advantage of change during China's economic reform to study the relative importance of organizational and environmental factors in producing innovative managerial response. I find that strategic choice predicted innovation in the early stages of reform, but environmental factors increased in salience over time. Intrafirm support, Communist Party connections, and a market orientation produced innovation early in reform. Simple imitation of others was also salient in early years. As reform progressed, managers increasingly imitated other profitable firms and drew on their own experience. My results inform an understanding of both the process by which innovation occurs and firm behavior in transition economies.